Redes sociales y conducta en los estudiantes de la Unidad Educativa “Tomás Oleas”. Colta. Chimborazo. Período quimestral: septiembre 2018-febrero 2019. - Estrella Montenegro, Erika Estefanía (2021)
Social networks and behavior were related, the beneficiaries were 30 students of First-year of parallel baccalaureate "A" of the Educational Unit "Tomás Oleas" in Colta cantòn, the methodology correspond to a quantitative approach for data tabulation , the reserach is of non-experimental design because the variables were not manipulated, for the objectives it was a basic field and cross-sectional research because it was applied only once occasion and in a determined time, the technique applied for data collection was the survey and as an instrument a questionnaire with six questions for each variable in which the results obtained were described and with which they could be correlated, the statistical program Spss was used for this calculation. The results obtained with their respective percentage were analyzed and interpreted, finally as a conclusion it can be said that social networks and behavior are related according to Pearson's correlation, which is statistically significant